New biobased chitosan-modified peach kernel shell composites and examining their behavior in different environmental conditions - Ahmetli, Gulnare; Soydal, Ulku; Kocaman, Suheyla; Özmeral, Nimet; Musayev, Nijat (International journal of biological macromolecules, 2024)
Bisphenol A-type epoxy (ER) is a versatile synthetic polymer preferred for composite materials but non-biodegradability raises challenges for composites recycling in particular. The present study first investigated the potential usability of peach kernel shells (PKSh) waste as fillers in ER to decrease the cost of composite materials and increase their bio-based content. Different chemical modifications were performed to increase the poor compatibility between the hydrophilic lignocellulosic filler and the hydrophobic polymer matrix. The modified PKShs were obtained by alkali treatment (NaOH-PKSh), coating with biopolymer chitosan (CTS-PKSh), and cross-linking of CTS with glutaraldehyde (GA@CTS-PKSh). The aging of composites is a highly topical subject given the increasing use of composites in structural applications in many industries. The composites' thermal stability and dynamic-mechanical properties in different aging environments (water, seawater, and hydrothermal) were examined. The order of the aging conditions in terms of their effects on the composite properties was: hydrothermal > water > seawater. The ER/GA@CTS-PKSh composite was the most resistant to all environmental conditions. The tensile strength of epoxy matrix (ER) increased max. by 7.78 %, 21.11 %, 42.22 %, and 45.46 % in the case of raw, NaOH-PKSh, CTS-PKSh, and GA@CTS-PKSh fillers, respectively. Composites showed higher absorption in both UV and visible regions. [Display omitted] •New biobased composites were prepared using different modified PKShs.•Water, seawater, and hydrothermal environments were used to age the composites.•Hydrothermal aging affected the composite properties more.•GA@CTS-PKSh composites exhibited higher properties than others.